Sistem Otomasi dan Monitoring Tanaman Hidroponik Berbasis Real Time OS - Pinandhita Yudhaprakosa; Sabriansyah Rizqika Akbar; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Wireless Sensor Network (WSN) can be applied to agriculture. But in terms of timeliness required execution in a timely manner in operation, to the maximum so as not to miss the expected time. Problems are often found, namely when scheduling caring for plants that are less regular. Scheduling method is needed called Real Time OS (RTOS). RTOS has scheduling and priority, where it will make the execution of data that has been determined according to its priority. This is called multi-tasking on sensors and actuators in several conditions. In accordance with the problem described above, the author designed a system of automation and monitoring of hydroponic plants based on real time OS, this system is designed to create a system that can monitor and automate the system. The system can automatically control water in hydroponic plants. The microcontroller used is Arduino Uno. For the method used in the system is Scheduling on the DHT11 sensor, Turbidity, Ultrasonic and actuator solenoid valve, mini water pump. DHT11 is used as an input that detects temperature and humidity, Turbidity is used to detect the degree of turbidity of water, Ultrasonic is used to detect water levels. Then the solenoid valve is used to remove water, a mini water pump is used to fill water. In this case, Thingspeak is used as a website to display temperature and humidity. After testing the RTOS successfully with a comparison without RTOS. Data is sent using Nodemcu. Nodemcu itself is a Wi-fi module that is used to send data from Arduino Uno to the Thingspeak website. Then it was also found that the results of the data accuracy test values found for RTOS found an error value of 0.95% and without RTOS 2.25%.